The Effect of Lamotrigine on Nav1.4 Voltage-Gated Sodium Channels - Yoshihiko Nakatani; Haruka Masuko; Taku Amano (Elsevier, 2013)
Lamotrigine (LTG) is an anticonvulsant drug used in the treatment of epilepsy and bipolar disorder and it has been known that LTG targets voltage-dependent sodium channels (VGSCs). In this study, we investigated the effect of LTG on the Nav1.4 Na+ current using HEK293 cells expressing mouse Nav1.4 VGSCs. By the treatment of LTG, Nav1.4 Na+ current was inhibited in a dose-dependent manner. Moreover, 100 μM LTG decreased Nav1.4 Na+ current around 40% and shifted the V1/2 of the inactivation curve to the hyperpolarization side by 20.96 mV. These findings suggest that LTG inhibits Nav1.4 Na+ current and modifies the kinetics of the inactivated state. Keywords:: lamotrigine, Nav1.4, voltage-clamp